Thigmomorphogenetic responses of an aquatic macrophyte to hydrodynamic stress - Schoelynck, Jonas; Puijalon, Sara; Meire, Patrick; Struyf, Eric (Frontiers in Plant Science, 2015)
The response of aquatic plants to abiotic factors is a crucial study topic, because the diversity of aquatic vegetation is strongly related to specific adaptations to a variety of environments. This biodiversity ensures resilience of aquatic communities to new and changing ecological conditions. In running water, hydrodynamic disturbance is one of the key factors in this context. While plant adaptations to resource stress (nutrients, light…) are well documented, adaptations to mechanical stress, particularly flow, are largely unknown. The submerged species Egeria densa was used in an experiment to detect whether the presence or absence of hydrodynamic stress causes plant thigmomorphogenetic responses (i) in terms of plant biogenic silica (BSi), cellulose and lignin concentrations, and (ii) in terms of plant strength. Plant silica concentrations, as well as lignin concentrations were significantly higher in presence of hydrodynamic stress. These physiological changes are accompanied by some significant changes in stem biomechanical traits: stem resistance to tensile forces (breaking force and breaking strength) and stiffness were higher for plants exposed to hydrodynamic stress. We conclude that the response of this aquatic plant species to mechanical stress is likely the explaining factor for a higher capacity to tolerate stress through the production of mechanically hardened shoots.